2021
DOI: 10.3389/fpsyg.2021.606083
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Psycholinguistic Study on the Subjective Feelings of Well-Being Outcomes of Foreign Language Learning in Older Adults From the Czech Republic and Poland

Abstract: Positive psychology has recently seen unprecedented rise and has reached vast achievements in the area of quality of life (QoL) improvement. The purpose of this study is to show that there are different aspects of well-being that make healthy older people motivated to learn a foreign language at a later age. The research was conducted in the Czech Republic and Poland in two groups of learners aged 55 years and more. The experimental group consisted of 105 Czech respondents who were targeted with an online ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Moreover, one of the studies (Hertzog et al, 2020 ) showed that older adults manifested a lower region of proximal learning due to their lack of belief in their ability to learn. Furthermore, according to Klimova et al ( 2021a ) and Pikhart et al, ( 2021 ), there is a correlation between the level of education, age, the sexes, and the number of languages studied during the response to the perceived effects of a foreign language learning impact.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, one of the studies (Hertzog et al, 2020 ) showed that older adults manifested a lower region of proximal learning due to their lack of belief in their ability to learn. Furthermore, according to Klimova et al ( 2021a ) and Pikhart et al, ( 2021 ), there is a correlation between the level of education, age, the sexes, and the number of languages studied during the response to the perceived effects of a foreign language learning impact.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether nine studies were detected. Four articles of the eight selected originated in the Czech Republic (Klimova et al, 2021a , 2021b ; Pikhart & Klimova, 2020 ; Pikhart et al, 2021 ). The five remaining studies are from Austria, Germany, Ukraine, and the USA (Grossmann et al, 2023 ; Grossmann et al, 2021 ; Hertzog et al, 2020 ; Pfenninger & Kliesch, 2023 ; Sandal et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results align with previous studies. For example, Klimova et al (2021) showed that older adults’ overall satisfaction and SWB were very high when they participated in foreign-language courses. Bo (2017) also showed that participation in learning activities was significantly and positively associated with SWB.…”
Section: Discussionmentioning
confidence: 99%